Youth weightlifting - A review on the risks, benefits, and long-term athlete development associated with weightlifting amongst youth athletes - Woods, B. A. K. (Journal of Australian Strength and Conditioning, 2019)
Youth participation in weightlifting is mostly safe, has a multitude of benefits, both physiological and psychological, and has long term applications to athletic development.